Estudio De Poblaciones De Plantas En Cuatro Líneas Promisorias De Soya (Glycine Max.) En La Zona De Montalvo Provincia De Los Rios, Ecuador - Ricardo X. Chávez Betancourt; Víctor Molina Barbotó; Jorge Franco Rivera; Joffre León Paredes; Maribel Vera Suarez; Rosa Elena Guillen Mora; Darío Dueñas Alvarado (European Scientific Journal, ESJ, 2017)
The objective of this research is to determine the agronomic performance of cultivars of soybean lines with different densities. It also aims to establish its optimum performance based on its interaction with people in the town of Montalvo. The materials used in this study include S-864 lines, S- 840, IT-10 725, and 112-27 under different population densities of about 250 000, 300 000, 350 000, and 400000 plants per hectare. The split plot design were three treatments (lines), four subtreatments (populations), and three replications. For the evaluation and comparison of means, Tukey test was used at a probability of 5%. The data evaluated in the study include: incidence of disease and lodging, height at first pod and harvest, days to flowering, number of branches per plant, number of grains per pod, pod number per plant, seed weight, and yield 100 kg / ha. According to the results of the study, it was determined that the growing IT-112-27 recorded the highest average plant height at first pod. It, however, has a population of 400000 plants/ha which was obtained in the line IT-112-27 tallest crop plant, lines S-840, and line IT- 112-27. They recorded the best averages in days to flowering, with a population of 350000 plants/ha. The S-864 line achieved the highest average days to harvest. Also, the variable branches per plant did not show statistical significance in its lines, populations of plants, and the number of grains per plant. Consequently, the highest value was recorded by S-840 which interacted with 250 000 plants/ ha. Cultivar S-840 had the highest number of pods per plant with 38.9 pods. However, while interacting with populations of 250,000 plants/ha, 37.2 pods was obtained. Line IT- 112-27 with 19.1 grams presented the highest weight of 100 seeds. The highest grain yield was shown in line IT- 112-27 with a population of 350000 plants/ha. Since line IT-112-27 was presented as the best production, we recommend the use of a good fertilizer, weed control, and pests and diseases control when planting during the dry or rainy season.